Safflower Oil (Carthamus tinctorius L.) Intake Increases Total Cholesterol and LDL-cholesterol Levels in an Experimental Model of Metabolic Syndrome - Santana,Lidiani Figueiredo (2017)
Abstract Background: Overweight has been considered an important public health problem. To reverse this situation, various types of treatment are proposed. The safflower oil (Carthamus tinctorius L.) has been used in the prevention/treatment of obesity. Objectives: The aim of this study was to evaluate the therapeutic effects of this oil in an experimental model of metabolic syndrome. Methods: Male Wistar rats initially received a highly palatable (HP) diet for ten weeks for validation of a metabolic syndrome model. Following confirmation, the animals were treated with a HP diet and soybean oil (HPSO) or safflower oil (HPSA) supplementation (1.0 mL/1000 g of animal weight). At the end of the experiment, the body composition, lipid profile and blood glucose levels of the animals were assessed. Student t test was used for statistical analysis. Results: In the first stage (induction of metabolic syndrome), the animals given the HP diet showed gain weight (p < 0.001), visceral adiposity (p = 0.001), and significantly higher levels of blood glucose (p = 0.001) and triglycerides (p = 0.03) than those of the control group. Also, there was a difference in liver weight (p = 0.01). These results demonstrate that the HP diet administration is an effective model for the experimental metabolic syndrome study. In the second stage, the animals of the HPSA group showed increased total cholesterol (p < 0.05) and LDL-cholesterol (p < 0.001) levels. Conclusion: Under the referred experimental conditions, the use of safflower oil can cause possible deleterious effects on the lipid profile in a metabolic syndrome experimental model.